Effectiveness of Tm S in Children with Cerebral Palsy - Yakubovna, Ergasheva Munisa (American Journal of Bioscience and Clinical Integrity, 2025)
Currently, research in pediatric neurology focuses on the effectiveness of non-invasive brain stimulation (NIBS) in treating various neurological diseases in children. Transcranial magnetic stimulation (TMS), as a type of NIBS, has the technical characteristics of being non-invasive and painless, in which electromagnetic principles are applied to brain areas and regulate the functions of various areas of the cerebral cortex by changing the excitability of neurons. Currently, TMS is increasingly used in the treatment of children with cerebral palsy (CP). TMS can improve motor function, relieve spasm, restore speech function in patients with CP, and change brain function by modulating developmental plasticity. The study involved 34 children with spastic diplegic cerebral palsy to demonstrate the effectiveness of transcranial magnetic stimulation (TMS) as a new method for restoring motor functions. After TMS, children with spastic diplegic cerebral palsy showed significant improvements in motor and speech activity.